Phase I Trial of Pyragrel, a Novel Thromboxane Synthetase Inhibitor, to Evaluate the Safety, Tolerability, and Pharmacokinetics in Healthy Volunteers - Zou, Chan; Zuo, Xiaocong; Huang, Jie; Hua, Ye; Yang, Shuang; Yang, Xiaoyan; Guo, Can; Tan, Hongyi; Chen, Jun; Chu, Zhaoxing; Pei, Qi; Yang, Guoping (Frontiers in Pharmacology, 2019)
Background and Objective: Inhibition of thrombosis and platelet aggregation through a thromboxane synthetase inhibitor proved to be an effective and promising treatment for cardiovascular and/or cerebrovascular disease (CCVD) patients. This phase I study evaluated the safety, tolerability and pharmacokinetics of sodium pyragrel, a novel thromboxane A2 synthetase inhibitor, in healthy volunteers. Methods: A total of 84 healthy Chinese volunteers were enrolled in the study and randomized into one of five dosing regimens of intravenous pyragrel, which were single ascending dose (30 to 300 mg), multiple doses [pyragrel 180 mg once daily on Day 1 and Day 6, twice daily from Day 2 to Day 5)], 3×3 Latin square crossover (60, 120, 240 mg) and a continuous dose (360 mg in 24 h), respectively. Plasma concentrations were determined using HPLC-MS/MS. Pharmacokinetics parameters were calculated with non-compartment analysis. Results: The maximum plasma concentrations of pyragrel were essentially reached at the end of the 3 h infusion. The pharmacokinetic process of pyragrel and two main metabolites (BBS and BJS) is linear over the 30-300 mg dose range, with no significant accumulation on multiple doses. The urinary excretion of pyragrel accounted for more than 70% of the total drug amount. Preliminary pharmacodynamic results demonstrated that the production of urinary 11-D-HTXB2 was time- and dose-dependently inhibit by single i.v. dose of pyragrel. Conclusions: Pyragrel was well tolerated after single ascending doses up to 300 mg, multiple doses of 180 mg and continuous administration of 360 mg within 24 h. No drug-related, serious adverse drug reactions occurred during the five-part study. The most common pyragrel-related adverse events (AEs) were total bilirubin (TB)/direct bilirubin (DB) elevations with a relatively low incidence rate and seemed to be dose independent. Given the acceptable safety and appropriate pharmacokinetic properties of sodium pyragrel proven in this study, continued clinical development is warranted. The study was registered at http://www.chictr.org.cn (ChiCTR-IID-16010159).